1989
DOI: 10.1590/s0037-86821989000300001
|View full text |Cite
|
Sign up to set email alerts
|

Terapêutica da fase crônica da infecção experimental pelo Trypanosoma cruzi com o Benzonidazol e o Nifurtimox

Abstract: Fifty-eight mice, chronically infected with different T. cruzi strains (Types II and III) were submitted to chemotherapy either with Nifurtimox (Bay 2502) or Benznidazole (Ro 7-1051). Twenty one mice were not treated and were used as infected controls. The duration of infection was from 90 to 400 days. Inocula varied from 1 x 10(4) to 5 x 10(4) blood forms. Treatment lasted for 90 days, doses being 200mg/kg/day during 4 days, followed by 50mg/kg/day for Nifurtimox and 100mg/kg/day for Benznidazole. Parasitolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 6 publications
2
11
0
1
Order By: Relevance
“…Discrepant data were also observed for BUG2148 cl1 and MN cl2 of genotype 39 and MVB cl8 and IVV cl4 of genotype 32. Similar results were previously described by Andrade et al (2), who demonstrated that T. cruzi I strains that were highly resistant to BZ and NFX during AP were partially susceptible to both drugs during CP.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Discrepant data were also observed for BUG2148 cl1 and MN cl2 of genotype 39 and MVB cl8 and IVV cl4 of genotype 32. Similar results were previously described by Andrade et al (2), who demonstrated that T. cruzi I strains that were highly resistant to BZ and NFX during AP were partially susceptible to both drugs during CP.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, during CP a different association between the zymodeme and the drug resistance pattern was found. Even strains highly resistant to BZ during AP, like T. cruzi I strains, were shown to be partially susceptible during CP, while no such differences were observed for T. cruzi II strains (2). Although the studies cited above have made significant contributions, they did not rely on a rigorous population genetics framework.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would lead to a reduction in the complications of the disease, especially those related to heart disease. Classical experimental studies in mice have already documented total or partial regression of early myocardial injuries and the prevention of cardiopathy with antiparasitic treatment (299) (300) . However, regression of inflammatory and fibrotic lesions, observed in experimental studies, has not been verified in the clinical context (20) .…”
Section: Treatment Of Chronic Phasementioning
confidence: 99%
“…However, treatment during the chronic phase promotes recovery in only 37% of cases, with few protective effects during the clinical course of the disease (6,7). However, some authors reported BNZ treatment as beneficial because the parasite is the major factor responsible for tissue lesions and the clinical course (8)(9)(10). Therefore, the usefulness of BNZ during the chronic phase is still undergoing investigation.…”
mentioning
confidence: 99%